2022
DOI: 10.22270/jddt.v12i1.5276
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Gongronema latifolium improves learning and memory in Swiss albino Mice

Abstract: Learning and memory are vital attributes of human intelligence. These processes underlie the very nature of our self-awareness, planning and execution of task. The number of people living with dementia worldwide is currently estimated at 35.6 million. About 80% of the world’s population depend on herbal remedies to curb mental disorders. This study aimed to investigate the effects of administration of ethanolic leaves extract of Gongronema latifolium (GL) on learning and memory in mice. Thirty (30) adult male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This result is in line with that reported by Osuagwu et al (2013) and Offor et al (2015); in their separate research, they observed higher concentration of flavonoids, phenols, tannins, and scarce quantity of alkaloids in the dried leaves of G. latifolium. The high increase in flavonoid and phenol contents recorded in the fruit of G. latifolium may provide antioxidant capacities to scavenge hydroxyl radicals protecting the cells against oxidative damage (Osuagwu et al, 2013;Ujong et al, 2022). Tannins extracted from G. latifolium fruit extract could inhibit food deterioration through inhibition of oxidative enzymes such as lipoxygenase (Eze and Nwanguma, 2013).…”
Section: Quantitative Constituents Of G Latifolium Fruit Extractmentioning
confidence: 99%
“…This result is in line with that reported by Osuagwu et al (2013) and Offor et al (2015); in their separate research, they observed higher concentration of flavonoids, phenols, tannins, and scarce quantity of alkaloids in the dried leaves of G. latifolium. The high increase in flavonoid and phenol contents recorded in the fruit of G. latifolium may provide antioxidant capacities to scavenge hydroxyl radicals protecting the cells against oxidative damage (Osuagwu et al, 2013;Ujong et al, 2022). Tannins extracted from G. latifolium fruit extract could inhibit food deterioration through inhibition of oxidative enzymes such as lipoxygenase (Eze and Nwanguma, 2013).…”
Section: Quantitative Constituents Of G Latifolium Fruit Extractmentioning
confidence: 99%
“…The body weights of animals were taken using an electronic weighing balance at the start and daily till the end of the experiment. The dose of GL leaf extract that was used in the present study was selected based on the outcome of the lethal dose (LD50: 1050 mg/kg) experiment in our laboratory (Ujong et al, 2022).…”
Section: Experimental Designmentioning
confidence: 99%
“…Gongronema latifolium (GL) is one of such plants that have potential phytochemicals with medicinal properties. GL is an edible rainforest plant (Ujong et al, 2022) belonging to the family of Asclepiadaceae. In sub‐Saharan Africa, the leaves of this plant are often used as a spicing agent in cuisines and as a medicinal herb (Showande et al, 2019).…”
Section: Introductionmentioning
confidence: 99%